Pengembangan Metode Pembelajaran Selin Activity dalam Pendidikan Jasmani untuk Meningkatkan Keterampilan Gerak Dasar Siswa - Sevesti Violin Wilujeng Herista; Nanik Indahwati; Pudjijuniarto; Sapto Wibowo; Anung Priambodo; Mochamad Ridwan (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
This study aimed to develop the Selin Activity learning method, determine its feasibility, and examine its effectiveness in improving the fundamental movement skills of Phase C elementary school students. This study employed a Research and Development (R&D) approach using the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The participants were fifth- and sixth-grade elementary school students. The feasibility of the product was evaluated by physical education experts, motor development experts, and practicing physical education teachers using validation instruments. The effectiveness of the product was assessed using the MOBAK 5–6 instrument, which measures two domains: object movement and self movement. Data were analyzed descriptively and further examined using the Wilcoxon Signed-Rank Test and effect size analysis with SPSS version 25. The findings indicated that Selin Activity was successfully developed as a circuit-based learning method consisting of six movement activities. The validation results showed that the product was considered feasible for implementation, receiving scores of 74% from physical education experts, 78% from motor development experts, and 91% from practicing physical education teachers. The effectiveness test revealed a significant improvement in students’ fundamental movement skills following participation in the Selin Activity program, with a significance value of 0.000 (p < 0.05). Furthermore, the effect size values of 0.863 for the object movement domain and 0.856 for the self movement domain indicated a large effect on the improvement of students’ fundamental movement skills. Based on these findings, it can be concluded that Selin Activity is a feasible and effective learning method for improving the fundamental movement skills of Phase C elementary school students. The method has the potential to serve as an alternative approach to physical education instruction by increasing students’ active engagement and supporting the development of movement competence more effectively. Keywords: Fundamental Movement Skills, Circuit-Based Learning Method, Physical Education